Pemanfaatan Media Sosial TikTok Sebagai Sarana Komunikasi Pemasaran: Analisis Pada Akun @infokulinerpati - Taniva, Diva; Try Purnomo, Danang; Paramita, Santi (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
Social media has become an important tool in modern marketing strategies. This research aims to analyze the marketing strategies implemented on the @infokulinerpati account to increase consumer engagement and interest. This research uses descriptive qualitative methods with content analysis to identify the marketing strategies implemented by the @infokulinerpati account. The research results show that creative and interactive content presented in short videos succeeds in attracting the audience's attention, increasing interaction, and utilizing the live stream feature can also have a very important impact on establishing good relationships directly with followers. The use of music and visual effects on TikTok is one of the main factors in the success of this marketing strategy. This research concludes that TikTok can be an effective marketing tool, especially to reach the younger generation as the main users of this platform.